THU0078 Concomitant use of conventional synthetic dmards and response to baricitinib. (15th June 2017) - Kavanaugh, A; Helt, C; Muram, D; Alam, J; Arora, V; Correia, AL Pinto; Torre, I de la; Vollenhoven, R van
Abstract : Background: Baricitinib (BARI), an oral JAK1/JAK2 inhibitor, is in development for patients (pts) with moderate to severe rheumatoid arthritis (RA). 1, 2 Objectives: This post-hoc analysis of two phase 3 studies assessed whether concomitant use of conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) altered the response or safety outcomes to BARI in RA pts and evaluated the effect of concomitant corticosteroid use on the efficacy of BARI. Methods: Pts with ≥6 swollen and tender joints and no prior biologic DMARD use were enrolled. In RA-BEAM (NCT01710358 ), methotrexate (MTX)-inadequate responder (IR) pts were randomised to PBO once daily (QD), BARI 4 mg QD, or adalimumab 40 mg biweekly. 1 In RA-BUILD (NCT01710358 ), csDMARD-IR pts were randomised to placebo (PBO) or BARI (2 or 4 mg) QD. 2 Pts continued background csDMARD (including MTX) therapy. This post-hoc analysis included the PBO (N=716) and BARI 4 mg (N=714) pts and assessed the number and type of concomitant csDMARDS and concurrent corticosteroid use. Results: 71%, 21%, and 6% of PBO pts were taking MTX alone, MTX + ≥1 other csDMARD, and non-MTX csDMARDs, respectively; in BARI 4 mg pts, the rates were 74%, 18%, and 6%, respectively. Oral corticosteroids were used in 56% of PBO and 55% of BARI pts at baseline; pts continued use throughout the studies. The differences in clinical efficacy between BARI 4 mg and PBO at 12 weeks was similar regardless of the number or type of csDMARDs concomitantly used (Table) or the concomitant use of corticosteroids (data not shown). The rates of serious adverse events and discontinuation due to adverse events were comparable regardless of the number or type of csDMARDs used (Table) or corticosteroid use. ACR20/50/70=20%, 50%, and 70% improvement in American College of Rheumatology criteria; csDMARDs=conventional synthetic disease-modifying antirheumatic drugs; DAS28-ESR=Disease Activity Score 28-erythrocyte sedimentation rate; MTX=methotrexate; SDAI=Simple Disease Activity Index. Conclusions: BARI has demonstrated clinical safety and efficacy in a wide range of pts, regardless of the number of concomitant csDMARDs or concomitant use of corticosteroids. References: Taylor PC et al. Arthritis Rheumatol 2015;67(S10):3927–3928. Dougados M et al. Ann Rheum Dis 2017;76:88–95. Disclosure of Interest: A. Kavanaugh Consultant for: Eli Lilly and Company, C. Helt Employee of: Eli Lilly and Company, D. Muram Employee of: Eli Lilly and Company, J. Alam Employee of: Eli Lilly and Company, V. Arora Employee of: Eli Lilly and Company, A. L. Pinto Correia Employee of: Eli Lilly and Company, I. de la Torre Employee of: Eli Lilly and Company, R. van Vollenhoven Grant/research support from: Abbvie, Amgen, BMS, GSK, Pfizer, Roche, UCB, Consultant for: Abbvie, Biotest, BMS, Celgene, Crescendo, GSK, Janssen, Eli Lilly and Company, Merck, Novartis, Pfizer, Roche, UCB, Vertex